Nikah Mut'ah: Kajian Atas Argumentasi Syi'ah - Machasin, Machasin (Musawa Jurnal Studi Gender dan Islam, 2002)
Temporary marriage or nikah mut'ah is a phenomenon that occurs within Islam. Nevertheless the ulama differ in their opinions of its validity. The majority of Sunni Muslims believe that this type of marriage was originally permitted but later forbidden. Whereas the Shi'ah group believe that contract marriage is permitted, and some of them even recommend it. Yet, it seems that the arguments they propose all have their weaknesses because temporary can still be disputed. Because of these problems, we should bring the issue of contract marriage back to the principles oflslamic teachings which hold human dignity in high esteem, value the ability of people to find the truth, and provide guidance to channel biological desires responsibly. As long as temporary marriage does not contradict these values the validity is maintained, but if it opposes these values then the prohibition cannot be denied.